A facile one-step synthesis of ZnO quantum dots modified poly(triazine imide) nanosheets for enhanced hydrogen evolution under visible light. Issue 88 (17th October 2016) - Zhang, Hui; Liu, Feng; Mou, Zhigang; Liu, Xiaofeng; Sun, Jianhua; Lei, Weiwei
Abstract : PTI/ZnO-QDs, a novel heterostructured photocatalyst, has been synthesized via a "one-pot" protocol, and exhibits significantly enhanced photocatalytic activity. Abstract : A heterojunction of crystalline poly(triazine imide) (PTI) nanosheets and ZnO quantum dots (QDs) (∼3 nm) was synthesized by a one-step ionothermal condensation of cyanamide. The resulting PTI/ZnO-QDs heterostructure exhibits a significantly enhanced H2 evolution to 63 times that of pure PTI and 3.4 times that of graphitic carbon nitride (g-C3 N4 ) under visible light.